Kleiber ratios and growth curves of African Black and Red Neck ostrich breeds and their crossbreeds - de Rezende, Marcos Paulo Gonçalves; Souza Carneiro, Paulo Luiz; Moretti, Riccardo; Mendes Araujo, Johnny Iglesias; Cardoso, Israel Luz [UNESP]; Araujo, André Campêlo; de Souza, Julio Cesar; Bozzi, Riccardo; Mendes Malhado, Carlos Henrique (Universidade Estadual de Londrina, 2021)
The selection of animals with lower production costs can be achieved by using feed efficiency and growth curve information. Kleiber ratio (KR) is an alternative option for discriminating against the animals that have the greatest weight gain about their final weight. Alternative feed efficiency and growth curves for ostriches of the African Black (AB) and Red Neck (RN) breeds and their crossbreeds (CB) were investigated using KR and Gompertz equation. Univariate and multivariate analyses were used. The highest adult weight was identified in the RN and CB. AB was more precocious than the RN and CB individuals. Only AB animals reached 75% of their mature weight at one year of age. At 180 days, AB showed better KR. AB was different from the others, mainly for KR at 90 days and 180 days. Considering multivariate analysis, AB animals were different from the others, regardless of sex, mainly for KR at 90 days and KR at 180 days. Other subgroups separated the animals by sex. In a market preferring animals of minor structure (smaller cuts) and greater precocity, it would be suitable to opt for AB. When animals with greater body structure (larger cuts) are desired, males RN and CR is the best option, however, it will be slaughtered with greater age and lower value for KR (may generate a bigger production cost). It is possible to obtain animals with precocity and high KR, being well represented by the AB breed.
Razão Kleiber e curva de crescimento para raças de avestruzes African Black e Red Neck e seus cruzamentos
Keywords: Degree of maturity; Feed efficiency; Multivariate analysis; Nonlinear model; Struthio camelus